KRITIK EPISTEMOLOGI ISLAM OLEH MUHAMMAD ABID AL-JABIRI DAN IMPLIKASINYA PADA ISLAMISASI PSIKOLOGI - Sulaiman, Ahmad; Syakarofath, Nandy Agustin; Kusmana, Kusmana (UIN Raden Mas Said Surakarta, 2024)
Jabiri's philosophical thought has had a very broad influence both at the global and national levels. The concept of reason is formed and active and the episteme trilogy allows a critical reading of Islamic law. It helps distinguish between the transcendent and absolute normative values ​​of Islam and the contextual historical and methodological side of Islam. Using Jabiri's thinking, this study will formulate a critique of the Islamization of Psychology movement that has been developing for a long time. The problem is that the Islamization of psychology works by consolidating the bayani episteme and making the bayani psychology dominant. This creates a theoretical dead end in Islamic psychology because it is bound by the text and context of the holy book, thereby ignoring the dynamics of modern science. It is also shown that other Islamic epistemes can give different forms to the Islamization of Science with the development that has been carried out by several Muslim scholars on a limited basis as an example. The implication is that Islamic psychology must present an alternative epistemological structure that overcomes old limitations before being followed by an Islamic psychology that is able to provide benefits throughout the ages.